Mechanical, electronic, and thermodynamic properties of zirconium carbide from first-principles calculations - 杨晓勇 鲁勇 郑法伟 张平 (Chinese physics B, 2015)
Mechanical, electronic, and thermodynamic properties of zirconium carbide have been systematically studied using the ab initio calculations. The calculated equilibrium lattice parameter, bulk modulus, and elastic constants are all well consistent with the experimental data. The electronic band structure indicates that the mixture of C 2p and Zr 4d and 4p orbitals around the Fermi level makes a large covalent contribution to the chemical bonds between the C and Zr atoms. The Bader charge analysis suggests that there are about 1.71 electrons transferred from each Zr atom to its nearest C atom. Therefore, the Zr-C bond displays a mixed ionic/covalent character. The calculated phonon dispersions of ZrC are stable, coinciding with the experimental measurement. A drastic expansion in the volume of ZrC is seen with increasing temperature, while the bulk modulus decreases linearly. Based on the calculated phonon dispersion curves and within the quasi-harmonic approximation, the temperature dependence of the heat capacities is obtained, which gives a good description compared with the available experimental data.